Advanced integration of LNG regasification power plant with liquid air energy storage: Enhancements in flexibility, safety, and power generation. (1st July 2020) - Qi, Meng; Park, Jinwoo; Kim, Jeongdong; Lee, Inkyu; Moon, Il
Graphical abstract: Highlights: LNG is re-gasified in two different ways during peak and off-peak times. High-grade LNG cold energy is used for air liquefaction to enhance power generation. Pressures of LNG vaporization and liquid air storage are minimized to 7 and 0.15 MPa. The highest specific daily net power output is achieved at 85.7–94.8 kJ/kgLNG . The economic advantages of the process are shown over other types of integrations. Abstract: Power plants for regasification of liquefied natural gas (LNG), integrated with liquid air energy storage (LAES), have benefits in terms of power generation flexibility to match the electricity demand profiles and increased operating profits from electricity arbitrage. However, issues with the flexibility and safety of this integration still remain. In addition, further improvements in power generation were identified from the use of high-grade LNG cold energy in LAES. Thus, this paper proposes a novel and advanced integration (denoted as LNG-LAES) for enhancements in flexibility, safety, and power generation. LNG is re-gasified in two different manners: it flows into a parallel two-stage regenerative Rankine cycle for conventional power generation during peak times or transfers high-grade cold energy to LAES for energy storage during off-peak times. Pressures of LNG vaporization and liquid air storage are minimized to 7 and 0.15 MPa to achieve an inherently safer design. The process assessment is performed considering possible demand and marketing scenarios, in which the LNG-LAES process exhibits the best performance in terms of power generation and economic benefits. In the base-case, the specific daily net power output increases up to 94.8 kJ/kgLNG and the electrical round trip efficiency of LAES achieves 129.2%. Moreover, the LNG-LAES process has design flexibility that the amount of LNG cold energy utilized in LAES can be varied at the design stage to maximize the operating profit corresponding to a specific electricity market scenario. The analyzes demonstrate that the proposed LNG-LAES process is both technically feasible and economically preferable for industrial applications.